2017
DOI: 10.1001/jamafacial.2016.1084
|View full text |Cite
|
Sign up to set email alerts
|

Dermatography (Medical Tattooing) for Scars and Skin Grafts in Head and Neck Patients to Improve Appearance and Quality of Life

Abstract: IMPORTANCE Dermatography (medical tattooing) is often overlooked as an adjuvant procedure to improve color mismatch in the head and neck area, and its effect on patient satisfaction and quality of life has not been evaluated, to our knowledge. OBJECTIVE To analyze the effect of dermatography on the subjective perception of the appearance of scars and skin grafts and the quality of life in head and neck patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(131 reference statements)
0
7
0
Order By: Relevance
“… 7-9 The Drost et al article is recommended for those with interest in viewing photographic examples of what is possible with this intervention for patients with head and neck cancer. 8 The treatment of hypopigmented scars through medical tattooing received high ratings of patient and physician satisfaction. Recent studies have integrated other professionals into the provision of medical tattoos.…”
Section: Resultsmentioning
confidence: 99%
“… 7-9 The Drost et al article is recommended for those with interest in viewing photographic examples of what is possible with this intervention for patients with head and neck cancer. 8 The treatment of hypopigmented scars through medical tattooing received high ratings of patient and physician satisfaction. Recent studies have integrated other professionals into the provision of medical tattoos.…”
Section: Resultsmentioning
confidence: 99%
“… 138 Specialized medical tattooing, known as dermatography, smoothens scars and improves aesthetics. 139 Treatment of top surgery scars with a novel topical spironolactone gel resulted in significantly higher patient satisfaction compared with silicone gel alone. Because testosterone could exacerbate scar tissue and keloid development, topical spironolactone could reduce scarring while avoiding undesired anti-androgenic systemic effects of oral spironolactone.…”
Section: Dermatological Considerations For Gender-affirming Surgerymentioning
confidence: 99%
“…It has been shown that providing effective treatment for skin conditions improves QoL. 15,35,42,58,[68][69][70][71][72] During chemotherapy and radiotherapy treatments, detecting and treating any skin toxicities early is essential. 73 Alongside treatments, focusing on techniques that patients already know including clothing choices, cleaning and emollients can help improve QoL.…”
Section: Evidence To Support a Holistic Treatment Approach Treatment Of The Conditionmentioning
confidence: 99%